Bureaucratic Reform Analysis through Performance of Hospital Employees - Suardi; Ermaya Suradinata; Kusworo; Ali Hanafiah Muhi (GoAcademica Research & Publishing, 2019)
This study examines the influence of bureaucratic reformation toward employee performance of the area general hospital Dr. R. Soedjono Selong in East Lombok Regency NTB Province with the number of respondents 270 employees, with stratified random sampling method. This research uses mixed method which combine quantitative and qualitative approach. Mixed method is used because in this research produce two kinds of data, taht is quantitative data and qualitative data. Mixed method is a research approach that combines or associates qualitatif forms, which is basically a combination of both qualitative and quantitative approach, so using a mixed can produce a comprehensive fact in researching the research problem, because in research the researcher has the freedom to use all data collection tool in accordance with the type of data required. Based the results of the study show that bureaucratic reformation variables significantly influence the employee performance (p value = 0,000 atau < 0,05) with a large value of the middle influence of 0,422 , which preves that the higher the level of bureaucratic reformation the better the employee performance. The work culture variables has a sigificant effect toword the employee performance (p value 0,001 atau < 0,05) with a large value of the low influence of 0,211, which preves that the higher the level of bureaucratic reformation the better the employee performance. The new findings generated from this research are the ARITMATIC model (Ability, Responsibility, Innovation, Team Work, Motivation, Agility, Technology, Information and Culture) abtained from the results of ASOCA analysis. Keywords: bureaucratic reformation, government, employee performance.